FILOSOFI TRI HITA KARANA DALAM MENGUNGKAP KONSEP AKUNTANSI HIJAU (STUDI FENOMENOLOGI) - Ni Putu Ayu Kusumawati; Ni Made Wisni Arie Pramuki; Ni Putu Trisna Windika Pratiwi (Faculty of Economics and Business, Universitas Warmadewa, 2023)
This article has been retracted with agreement of the journal editors. The retraction is due to a significant overlap with an article by the same authors that has been published in another journal (International Journal of Trends in Accounting Research). This constitutes a case of duplicate publication, which is a breach of our journal's publication ethics policy. The authors apologize to the readers and editors of both journals for this oversight. The journal is committed to upholding the integrity of the scientific record.